Therapeutic hypothermia reduces cortical inflammation associated with utah array implants. (28th April 2020) - Dugan, Elizabeth A; Bennett, Cassie; Tamames, Ilmar; Dietrich, W Dalton; King, Curtis S; Prasad, Abhishek; Rajguru, Suhrud M
Abstract: Objective. Neuroprosthetics hold tremendous promise to restore function through brain-computer interfaced devices. However, clinical applications of implantable microelectrodes remain limited given the challenges of maintaining neuronal signals for extended periods of time and with multiple biological mechanisms negatively affecting electrode performance. Acute and chronic inflammation, oxidative stress, and blood brain barrier disruption contribute to inconsistent electrode performance. We hypothesized that therapeutic hypothermia (TH) applied at the microelectrode insertion site will positively modulate both inflammatory and apoptotic pathways, promoting neuroprotection and improved performance in the long-term. Approach. A custom device and thermoelectric system were designed to deliver controlled TH locally to the cortical implant site at the time of microelectrode array insertion and immediately following surgery. The TH paradigm was derived from in vivo cortical temperature measurements and finite element modeling of temperature distribution profiles in the cortex. Male Sprague-Dawley rats were implanted with non-functional Utah microelectrodes arrays (UMEA) consisting of 4 × 4 grid of 1.5 mm long parylene-coated silicon shanks. In one group, TH was applied to the implant site for two hours following the UMEA implantation, while the other group was implanted under normothermic conditions without treatment. At 48 h, 72 h, 7 d and 14 d post-implantation, mRNA expression levels for genes associated with inflammation and apoptosis were compared between normothermic and hypothermia-treated groups. Main results. The custom system delivered controlled TH to the cortical implant site and the numerical models confirmed that the temperature decrease was confined locally. Furthermore, a one-time application of TH post UMEA insertion significantly reduced the acute inflammatory response with a reduction in the expression of inflammatory regulating cytokines and chemokines. Significance. This work provides evidence that acutely applied hypothermia is effective in significantly reducing acute inflammation post intracortical electrode implantation.